Leveraging sponsorships to meet organizational marketing objectives : a case study of a consumer packaged good product with the super bowl - Olejniczak, Michael; Aicher, Thomas J. (London : Human Kinetics, Inc., 2012)
The sponsorship landscape has become increasingly cluttered, making it difficult for brands to stand out amongst ubiquitous sponsors. The National Football League (NFL) and the NFL Super Bowl have exemplified the marketing opportunities, business potential, and sponsorship challenges present in large-scale sporting events. In this case study, we present a fictitious consumer packaged goods beverage company, Staz, and their sponsorship of the NFL Super Bowl. Through the case study, we outline the objectives Staz is attempting to attain through its partnership with the NFL Super Bowl, as well as the activities they employed at national, local and site specific levels. Throughout the case, we present challenges brought on by Staz's competitors, shortfalls in Staz's hospitality activities, and the under-utilization of social media during their Super Bowl sponsorship campaign. The reader's goal is to recognize the activities Staz executed well, while idealizing solutions for the brand's less effective activation efforts.
Originally published in Olejniczak, M., & Aicher, T.J. (2012). Leveraging sponsorships to meet organizational marketing objectives: A case study of a consumer packaged good product with the Super Bowl. Case Studies in Sport Management, 1(1), 76-84. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sports sponsorship -- Case studies; Special events -- Marketing -- Case studies